Guillain-Barré Syndrome In Pregnancy - Fajar Sekti Reliyana; Retnaningsih Retnaningsih (Medica Hospitalia : Journal of Clinical Medicine, 2020)
Background: Guillain-Barré Syndrome (GBS) is an acute demyelinating polyadiculopathy that usually present as progressive and symmetrical muscle weakness accompanied by absence or loss of deep tendon reflexes. This has been associated with various infectious agents, such as Campylobacter jejuni and usually occurs after 2-4 weeks after respiratory or gastrointestinal diseases. Estimated general incidence in population was 0.75-2: 100,000. Pregnancy can increase risk of GBS. The diagnostic criteria of GBS consist of clinical, laboratory and electrophysiological tests. Developing treatments such as plasmapheresis and intravenous immunoglobulin (IVIG) are relatively safe in pregnancy. Time and methode of delivery are based on obstetric indications and depend on maternal and fetal status. Purpose: The condition is rare in pregnancy and only few cases have been reported in literature. Appropiate management of pregnant patients with GBS is needed. Case report: We presented the case of a 20-year-old woman, with a 20-week pregnancy. She had experienced various complications from her GBS such as syndrome of inapropriate antidiuretic hormone secretion (SIADH), dysphagia, type 2 respiratory failure, and infectious during hospital treatment. The termination of pregnancy was carried out at 34 weeks with consideration of maternal and fetal conditions. She delivered a healthy baby. Conclusion: GBS in pregnancy must be handled by a multidisciplinary team involving neurologists, obstetricians, internist, and anesthetists. Keywords: Gullain Barre syndrome, pregnancy, intensive care management, SIADH, Intraveva Immunoglobulin , plasmapharesis